Structures of paediatric pain management: a PERUKI service evaluation study - Mark D Lyttle; Stuart Hartshorn; Sheena Durnin; Michael J Barrett (BMJ Publishing Group, 2021)
Background Pain is very common in childhood emergency department (ED) attendances, but is under-recognised and undertreated. Sequential national paediatric analgesia audits demonstrate suboptimal outcomes in several domains. The Donabedian framework examines the structures, processes and outcomes to evaluate quality of care. To date there has been no network-level exploration of structures supporting analgesic practices or attempts to address failure to attain national standards.Objective To benchmark current variation in assessment and management of childhood pain at network level.Methods Online survey distributed between December 2016 and January 2017 exploring health system structures including pain score tools, pain assessment/protocols, training, practice guidelines and analgesic agent usage. We explored structures, processes and outcomes to identify interventions, and their potential effectiveness and feasibility.Results In total 95% (38/40 sites) responded, including 25 tertiary (66%) and 13 secondary hospitals (34%), with a total annual paediatric ED census of 1 225 000 (range 11 500-65 000). Availability of analgesics varied included topical wound anaesthesia in 29/38 sites (76%), oral diclofenac sodium in 22/38 sites (58%) and tramadol in 16/38 sites (42%). Pain assessment was mandatory in initial assessment in 34/38 sites (89%), and 18/38 sites had a policy on frequency of pain assessment (47%). Local guidance aligned with national guidance in 21/38 sites (55%). There was no staff training at induction/orientation in 14/38 sites (37%) and no mandatory competencies in pain management in 23/38 sites (61%). Play specialist services were available in 21/38 sites (55%).Conclusion Despite national guidance and recommendations from multiple audits, there are substantial variations in structures relating to pain assessment and management across sites. The lack of uniformity is a likely root cause for the persistent suboptimal practices identified by serial national audits. A whole system and person-centred approach to improving pain outcomes by utilising effective interventions seeks to improve paediatric pain outcomes.